6‐Phenylhexyl silane derivatized, sputtered silicon solid phase microextraction fiber for the parts‐per‐trillion detection of polyaromatic hydrocarbons in water and baby formula. Issue 14 (12th June 2021) - Patel, Dhananjay I.; Roychowdhury, Tuhin; Shah, Dhruv; Jacobsen, Collin; Herrington, Jason S.; Hoisington, Jason; Myers, Colton; Salazar, Bryan G.; Walker, Amy V.; Bell, David S.; Linford, Matthew R.
Abstract: We report the fabrication of 6‐phenylhexylsilane derivatized, sputtered silicon, solid phase microextraction fibers that show parts per trillion detection limits for polyaromatic hydrocarbons, and negligible carry over and phase bleed. Their fabrication involves sputtering silicon on silica fibers under various conditions. Six different fibers were evaluated by generating three different thicknesses of sputtered silicon at two different throw distances, which altered the morphologies of the silicon surfaces. All of the fibers were coated with similar thicknesses of 6‐phenylhexylsilane (ca. 2 nm). These fibers were characterized with multiple analytical techniques. The optimum fiber configuration was then used to analyze polyaromatic hydrocarbons via direct immersion, gas chromatography mass spectrometry. Our best fiber for the extraction of low molecular weight polyaromatic hydrocarbons in water had similar performance to that of a commercial fiber. However, our fiber demonstrated ca. 3 times the extraction efficiency for higher molecular weight polyaromatic hydrocarbons. In addition, it outperformed the commercial fiber by showing better linearity, repeatability, and detection limits. A method for analyzing polyaromatic hydrocarbons in baby formula was developed, which showed very good linearity (0.5–125 ppb), repeatability (2–26%), detection limits (0.12–0.81 ppb), and recoveries (103–135%). In addition, our fiber showed much less (negligible) carry over and phase bleed than the commercially available fibers.